Integrated management enhances crop physiology and final yield in maize intercropped with blackgram in semiarid South Asia - Varatharajan, T.; Dass, Anchal; Choudhary, Anil K.; Sudhishri, S.; Pooniya, V.; Das, T. K.; Rajanna, G. A.; Prasad, Shiv; Swarnalakshmi, Karivaradharajan; Harish, M. N.; Dhar, Shiva; Singh, Raj; et al. (Frontiers in Plant Science, 2022)
Photosynthesis, crop health, and dry matter partitioning are among the most important factors influencing crop productivity and quality. Identifying variation in these parameters may help discover the plausible causes for crop productivity differences under various management practices and cropping systems. Thus, a two-year (2019–2020) study was undertaken to investigate how far the integrated crop management (ICM) modules and cropping systems affect maize physiology, photosynthetic characteristics, crop health and productivity in a holistic manner. The treatments included nine main-plot ICM treatments [ICM1 to ICM4 - conventional tillage (CT) based; ICM5 to ICM8 - conservation agriculture (CA) based; ICM9 - organic agriculture (OA) based] and two cropping systems viz., maize–wheat and maize+blackgram–wheat in sub-plots. The CA-based ICM module, ICM7 resulted in significant (p<0.05) improvements in the physiological parameters viz., photosynthetic rate (42.25; 42.86 µ mol CO2 m-2 sec-1), transpiration rate (9.84; 9.92 m mol H2O m-2 sec-1) and net assimilation rate (2.84; 2.77 mg cm-2 day-1), crop health [NDVI (0.77; 0.78), chlorophyll content (52.9; 53.1)], dry matter partitioning towards grain and finally increased maize crop productivity (6.60; 6.71 t ha-1) by 13.4–14.2 and 27.3–28.0% over CT and OA-based modules. For maize equivalent grain yield (MEGY), the ICM modules followed the trend as ICM7>ICM8>ICM5>ICM6>ICM3>ICM4>ICM1>ICM2>ICM9. Multivariate and PCA analyses also revealed a positive correlation between physiological parameters, barring net assimilation rate, and both grain and stover yields. Our study proposes an explanation for improved productivity of blackgram-intercropped maize under CA-based ICM management through significant improvements in physiological and photosynthetic characteristics and crop health. Overall, the CA-based ICM module ICM7 coupled with the maize+blackgram intercropping system could be suggested for a wider and adoption to enhance the maize production in semi-arid regions of India and similar agro-ecologies across the globe.